Trans-dimensional Bayesian electromagnetic inversion for geothermal reservoir characterization in South China: Uncertainty analysis of subsurface conductivity recovered from CSAMT data - Shengqi Tian; Peng Xue; Rongwen Guo; Jianxin Liu; Keke Zhou; Yongfei Wang; Jihai Mo; Jianjian Li; Heming Su (Geothermics, 2026)

An integrated source–exposure–transport framework for risk-oriented management of mining-impacted groundwater contamination - Chang Liu; Yimin Sang; Fan Feng; Tingyu Yang; Qingyue Wang; Yanwei Wang; Heming Wang; Fujun Ma; Qingbao Gu (Journal of Environmental Chemical Engineering, 2026)

Machine learning-based geographical origin discrimination of Smilax china - Boyuan Xu; Haotian Zhong; Yan Wang; Rui Liu; Xiao Huang; Heming Wu; Lei Wang; Aiping Deng; Yong Xiao; Kun Yu (Journal of Applied Research on Medicinal and Aromatic Plants, 2026)

Canopy gap disturbance restructures growth-mortality trade-offs of dominant canopy species in the understory - Shiwei Yu; Xuyang Zhu; Huimin Yin; Qingsong Yang; Shan Jiang; Qiuwu Yu; Xiwen Zheng; Jianan Wang; Heming Liu; Xihua Wang (Forest Ecology and Management, 2026)

TianGong database—an open-source, ILCD entry-level life cycle unit process database of china - Ming Xu; Weiqiang Chen; Yutao Wang; Lei Shi; Zhi Cao; Huimin Chang; Chang Chen; Xiangbin Ding; Jianwei Du; Huabo Duan; Kai Fang; Cuiyang Feng; et al. (Journal of Industrial Ecology, 2026)

Hybrid evolutionary framework with multiple fragmentation strategies and reinforcement learning for multi-objective molecule generation - Meijia Song; Lian Shen; Heming Jia; Juan Liu; Xiangrong Liu (Swarm and Evolutionary Computation, 2026)

Detailed investigation and potential instability analysis based on FLAC3D-Massflow: a case study of Majia landslide - Heming Ren; Mingtao Ding; Shuang Liu; Jianbo Wu; Haiguang Cheng (Bulletin of Engineering Geology and the Environment, 2026)

Stability of β-cyclodextrin interface-modified iron-carbon composite and its migration in porous media - Kangping Huang; Tianwen Zheng; Xinyue Li; Ziyin Yang; Ruoxi Li; Yizhou Liu; Naijin Wu; Moxi Wang; Liqin Zhi; Huilong Luo; Wenxia Wei; Peizhong Li; et al. (Journal of Environmental Chemical Engineering, 2025)

Characteristics of atmospheric CH4, CO2 and CO at a suburban coastal site in Hong Kong - Wai Ming Chan; Dasa Gu; Ka Fung Leung; Yuchen Mai; Sin Ka Mak; Xin Li; Xiangyunong Cao; Zhenxing Liang; Tsz Ching Tse; Zijie Xu; Hao Sun; Heming Bai; et al. (Atmospheric Environment, 2025)

Advanced design principles for wireless ingestible capsules towards gastrointestinal health monitoring - Feifei Lin; Heming Xu; Weiwei Zhao; Shujuan Liu; Qiang Zhao (Science Bulletin, 2025)

Long-term removal characterization of trichloroethylene from groundwater using sustained-release iron-carbon composite: Investigations through batch and column experiments - Kangping Huang; Tianwen Zheng; Xinyue Li; Ziyin Yang; Ruoxi Li; Yizhou Liu; Wenxia Wei; Yimin Sang; Heming Wang (Environmental Research, 2025)

Synergistic activation mechanisms of peracetic acid and applications in complex water matrices - Xiaojuan Bai; Shuo Qin; Heming Liu; Bowen Zhu (Chemical Engineering Journal, 2025)

Internal electric field and atomic-level interface modulation of V-MoS2/ZnIn2S4 heterojunction for efficient photocatalytic Uranium(VI) removal - Zhijian Zheng; Zifang Ye; Haiwei Qiu; Hongyi Wang; Xizao Wang; Heming Zhu; Zhian Wang; Youqun Wang; Zhimin Dong; Zhibin Zhang; Yibao Liu; Yunhai Liu (Journal of Environmental Chemical Engineering, 2025)

Predicting the flavor potential of green coffee beans with machine learning-assisted visible/near-infrared hyperspectral imaging (Vis-NIR HSI): Batch effect removal and few-shot learning framework - Minping Wu; Zhuangwei Shi; Haiyu Zhang; Rui Wang; Jiayi Chu; Shao Quan Liu; Heming Zhang; Hai Bi; Weihua Huang; Rui Zhou; Chenhui Wang (Food Control, 2025)

Expert consensus on cryosurgery therapy of mucosal melanoma on head and neck - Yadong Wu; Guoxin Ren; Moyi Sun; Zhangui Tang; Longjiang Li; Jian Meng; Zhijun Sun; Shaoyan Liu; Yue He; Wei Shang; Bo Li; Jie Zhang; et al. (Cryobiology, 2025)

Effect of static magnetic field-assisted repeated freezing and thawing on quality characteristics, microstructure, and myofibrillar protein properties of lamb meat - Jinxiao Liu; Wang Heming; Pengfei Du; Weiting Wang; Yaobo Liu; Guoyuan Xiong; Kun Yu; Yanli Ma (Innovative Food Science & Emerging Technologies, 2025)

Abundant taxa enhanced stability of fungal communities according to reduced nitrogen fertilization - Heming Han; Bo Zhang; Hao Liu; Yue Li; Xu Weidong; Liting Zhang; Hui Cao; Feng Wang (Soil and Tillage Research, 2025)

In situ synthesis of MIL-101 on carboxyl-functionalized SBA-16: Preparation and catalytic performance in the Knoevenagel condensation reaction under mild conditions - Chunlai Liu; Na Wang; Zelin Meng; Mingyang Song; Heming Zhao; Jianglei Hu; Fengwei Shi (Journal of Environmental Chemical Engineering, 2025)

Prediction of Pharmacoresistance in Drug-Naïve Temporal Lobe Epilepsy Using Ictal EEGs Based on Convolutional Neural Network - Yiwei Gong; Zheng Zhang; Yuanzhi Yang; Shuo Zhang; Ruifeng Zheng; Xin Li; Xiaoyun Qiu; Yang Zheng; Shuang Wang; Wenyu Liu; Fan Fei; Heming Cheng; et al. (Neuroscience Bulletin, 2025)

Reapplication of glyphosate mitigate fitness costs for soil bacterial communities - Hao Liu; Cunzhi Zhang; Bo Zhang; Weidong Xu; Ruoling Zhang; Liting Zhang; Yue Li; Heming Han; Hui Cao (Journal of Environmental Management, 2025)

The evolution of research at the intersection of industrial ecology and artificial intelligence - Yongyue Gong; Fengmei Ma; Heming Wang; Asaf Tzachor; Wenju Sun; Junming Zhu; Gang Liu; Heinz Schandl (Journal of Industrial Ecology, 2025)
The intersection of artificial intelligence (AI) and industrial ecology (IE) is gaining significant attention due to AI's potential to enhance the sustainability of production and consumption systems. Understanding the current state of research in this field can highlight covered topics, identify trends, and reveal understudied topics warranting future research. However, few studies have systematically reviewed this intersection. In this study, we analyze 1068 publications within the IE–AI domain using trend factor analysis, word2vec modeling, and top2vec modeling. These methods uncover patterns of topic interconnections and evolutionary trends. Our results identify 71 trending terms within the selected publications, 69 of which, such as “deep learning,” have emerged in the past 8 years. The word2vec analysis shows that the application of various AI techniques is increasingly integrated into life cycle assessment and the circular economy. The top2vec analysis suggests that employing AI to predict and optimize indicators related to products, waste, processes, and their environmental impacts is an emerging trend. Lastly, we propose that fine‐tuning large language models to better understand and process data specific to IE, along with deploying real‐time data collection technologies such as sensors, computer vision, and robotics, could effectively address the challenges of data‐driven decision‐making in this domain.

Revealing global supply risk of critical minerals essential for low-carbon energy technologies - Xinran Xing; Yawei Huang; Yao Wang; Heming Wang; Peng Wang; Tao Dai; Gang Liu; Asaf Tzachor (Journal of Cleaner Production, 2025)

Discovery of a polyester polyurethane-degrading bacterium from a coastal mudflat and identification of its degrading enzyme - Liting Zhang; Kaixun Cao; Hao Liu; Yuwei Wang; Bo Zhang; Heming Han; Zhongli Cui; Hui Cao (Journal of Hazardous Materials, 2025)

Role of hepatocyte-specific FOXO1 in hepatic glucolipid metabolic disorders induced by perfluorooctane sulfonate - Jing Yang; Longfei Li; Ziwen An; Yi Lv; Ran Li; Jing Li; Mingmei Guo; Heming Sun; Huiling Yang; Lei Wang; Yi Liu; Huicai Guo (Environmental Pollution, 2025)

Hybrid multi-stage steel footprinting unveils a more interdependent material foundation of the global economy - Xinyi Li; Chao Zhang; Xue Yang; Ziqian Xia; Zhi Cao; Peng Wang; Heming Wang; Tao Wang; Gang Liu; Wei-Qiang Chen (Ecological Economics, 2025)

Research on a new standardization method for milk FT-MIRS on different instruments based on agglomerative clustering and application strategies - Yikai Fan; Zhuo Yang; Guochang Yang; Chunfang Li; Xiaoli Ren; Chu Chu; Tingting Liu; Gang Liu; Wenjuan Bai; Heming Sui; Shujun Zhang (Computers and Electronics in Agriculture, 2024)

Material demand and recycling potential driven by wind power expansion in China - Zhi Wang; Congliang Hu; Heming Wang; Tao Dai; Xiaozhu Xu; Litao Liu (Journal of Environmental Management, 2024)

Regional water-energy-carbon footprint in the context of sustainable development based on EE-MRIO: cases of Jiangsu, Zhejiang and Shanghai - Huanyu Wang; Qiang Yue; Rui Liu; Yujie Zhang; Heming Wang; Qi Wang (Environment, Development and Sustainability, 2024)

Electro-mechano transduction of stacked triboelectric nanogenerator considering wave force: Modeling, validation and applications - Chen Cao; Fan Shen; Chuanfu Xin; Qin Zhang; Qiwei Zheng; Ying Gong; Heming Liu; Yan Peng; Zhongjie Li (Chemical Engineering Journal, 2024)

Research on copper flow and environmental load in China's new infrastructure industry for carbon neutrality - Yuqi Lu; Guangxin Liu; Qiang Yue; Yingjie Fu; Heming Wang; Zhihe Dou; Yisong Wang; Tao Du (Journal of Cleaner Production, 2024)

Competitive relationships due to similar nutrient preferences reshape soil bacterial metacommunities - Heming Han; Hao Liu; Bo Zhang; Yue Li; Chuanhai Li; Hui Cao (Science of The Total Environment, 2024)

The influence of simulated weightlessness on the composition and function of gut microbiota and bile acid metabolism products - Min Wang; Sheng Chen; Changqing Zhong; Lei Liu; Guodong Wang; Xin Huang; Xiaoman Yang; Heming Yang; Lianyong Li (Life Sciences in Space Research, 2024)

Contrasting graphitization differences between vitrinite and inertinite based on high-temperature and high-pressure experiments - Liu Zhifei; Cao Daiyong; Chen Gaojian; Chen Qingtong; Zhao Heming (Fuel, 2024)

Multinational dynamic steel cycle analysis reveals sequential decoupling between material use and economic growth - Xue Yang; Chao Zhang; Xinyi Li; Zhi Cao; Peng Wang; Heming Wang; Gang Liu; Ziqian Xia; Dajian Zhu; Wei-Qiang Chen (Ecological Economics, 2024)

A self-adaptive parallel image stitching algorithm for unmanned aerial vehicles in edge computing environments - Xin Xu; Li Zhang; Jibo Yue; Heming Zhong; Ying Wang; Jie Liu; Yanhui Lu; Hongbo Qiao (International Journal of Remote Sensing, 2024)

Technology transition strategies for textile-dyeing sludge management in China from the environmental and economic perspectives - Yongyue Gong; Fang Liu; Hanqiao Liu; Heming Wang; Yuxuan Zhao; Yanfei Lin (Sustainable Production and Consumption, 2023)

Does environmental regulation promote corporate green investment? Evidence from China’s new environmental protection law - Sheng Liu; Heming Liu; Xiuying Chen (Environment, Development and Sustainability, 2023)

Techno-economic assessment and exergy analysis of iron and steel plant coupled MEA-CO2 capture process - Yuhang Yang; Tao Du; Yingnan Li; Qiang Yue; Heming Wang; Liying Liu; Shuai Che; Yisong Wang (Journal of Cleaner Production, 2023)

An EGCG-mediated self-assembled micellar complex acts as a bioactive drug carrier - Chao Liu; Hao Wu; Hongxia Duan; Yan Hou; Shuangqing Wang; Yanhong Liu; Xintong Zhang; Heming Zhao; Liming Gong; Hongshuang Wan; Bowen Zeng; Xiuquan Quan; et al. (Food Chemistry, 2023)

Evaluating and optimizing PM2.5 stations in Yangtze River Delta from a spatial representativeness perspective - Heming Bai; Wenkang Gao; Myeongsu Seong; Rusha Yan; Jing Wei; Chong Liu (Applied Geography, 2023)

Characterization of freezability-associated metabolites in boar semen - Heming Sui; Mei Sheng; Haiqin Luo; Gang Liu; Fei Meng; Zubing Cao; Yunhai Zhang (Theriogenology, 2023)

Recyclable molten-salt-assisted synthesis of N-doped porous carbon nanosheets from coal tar pitch for high performance sodium batteries - Shiwei Wei; Xiaoyang Deng; Wei Li; Kai Liu; Jianxing Wang; Heming Zhao; Xiaoguang Wang (Chemical Engineering Journal, 2023)

What Iodine Intervention Measures Should Be Taken in Different Water Iodine Areas? Evidence from a Cross-sectional Chinese Survey - Yang Du; Peng Liu; Fangang Meng; Lijun Fan; Qingzhen Jia; Weidong Li; Wen Jiang; Jing Ma; Heming Zheng; Peihua Wang; Dianjun Sun; Hongmei Shen (Biological Trace Element Research, 2022)

Materials footprint of household consumption in China - Jingru Liu; Haotong Wu; Xin Tian; Heming Wang; Yinglei Wu (Journal of Industrial Ecology, 2022)
China has been witnessing profound changes in the consumption behaviors of its population during the last several decades. To better gauge the current consumption structure of Chinese households and investigate the burden exerted by consumption on resources, we calculated the household material footprint (HMF) in China within the individual consumption classification framework developed by the United Nations. HMF is the only life‐cycle‐based indicator adopted into the 2030 Agenda for Sustainable Development. Four types of raw materials and 15 representative consumption divisions were analyzed in this research. The total HMF in China increased by 103% from 1992 to 2017, although the per capita HMF remains lower than the global average. The per capita HMF growth in rural and urban areas differs, with urban citizens consuming 2.8 more metric tons of resources than rural residents as of 2017. The HMF of all materials studied shows a rising trend, especially for metal ores, which underpins the real estate and auto industries. Food‐related consumption is the main contributor to the HMF in China, while consumption of housing and transportation has less proportion yet more growth potential compared with developed countries. This study adds to the literature of studies on the consumption behaviors and domestic demands of China and has further methodologically significant meaning for similar studies in other countries and practical value for policymakers. Overall, this study demonstrates that despite an upsurge in consumption behaviors and gratifying economic records, the incurred resource and environmental burden may fuel risks for sustainable development.

Genome-wide Identification and Expression Pattern Analysis of the HD-Zip Transcription Factor Family in Pineapple (Ananas Comosus) - Qiao Zhou; Liping Liu; Han Cheng; Zeyun Li; MyatHnin Wai; Tiantian Luo; Xingyue Jin; Heming Zhao; S. V. G. N. Priyadarshani; Yuan Qin (Tropical Plant Biology, 2021)

Liver sinusoidal endothelial cells are implicated in multiple fibrotic mechanisms - Heming Ma; Xu Liu; Mingyuan Zhang; Junqi Niu (Molecular Biology Reports, 2021)

Bone Mineral Density in Population Long-Term Exposed to Rare Earth Elements from a Mining Area of China - Heming Liu; Haiyan Liu; Zenghua Yang; Kunzheng Wang (Biological Trace Element Research, 2021)

Preparation of heterogeneous Fenton catalyst γ-Cu-Ce-Al2O3 and the evaluation on degradation of phenol - Mei Li; Xinyu Gao; Heming Liu; Hongbo Wang; Qian Zhao; Ning Wang (Environmental Science and Pollution Research, 2020)

Cryptic phylogeographic history sheds light on the generation of species diversity in sky‐island mountains - Kai He; Eliécer E. Gutiérrez; Neander M. Heming; Klaus‐Peter Koepfli; Tao Wan; Shuiwang He; Wei Jin; Shao‐Ying Liu; Xue‐Long Jiang (Journal of Biogeography, 2019)
Aim The aim of this study was to conduct comprehensive phylogeographic and demographic analyses to examine the degree to which topographic and climatic conditions have affected the patterns of diversification and migration in a strictly montane inhabitant, the montane long‐tailed mole ( Scaptonyx fusicaudus ). Location The mountains of south‐western China and adjacent mountains including Mts. Bashan, Dalou and Qinling also known as the sky islands in south‐western China. Taxon The long‐tailed mole ( S. fusicaudus ), a semi‐fossorial mammal distributed in the sky islands of south‐western China, is a relict species and the sole representative of the tribe Scaptonychini. Methods We sequenced one mitochondrial and six nuclear genes from 113 samples across the species’ range. We estimated phylogenetic relationships and divergence times, conducted genetic structuring and species delimitation using multiple approaches and used Approximate Bayesian Computation to test potential gene flow. We conducted ecological niche modelling to predict the species’ potential distribution in the present, the last glacial maximum and the last interglacial (LIG). Results The species comprises a minimum of 17 operational taxonomic units which are isolated in different mountain ranges. The lowlands and large rivers act as barriers to dispersal, and have isolated evolutionary lineages for up to 11 million years. Long‐distance dispersal is evident among a few discrete montane archipelagos. Suitable climatic conditions during the LIG are limited to only a few sites, thus geographically restricting climatic stable areas across geological periods (from the LIG to the present). Main conclusions For low‐vagility species, the complex topography of the sky islands has promoted exceptional diversification through a combination of eco‐environmental stability as well as geographic fragmentation. The mountains have acted as a buffer against climate change, and have provided continuously suitable habitats for S. fusicaudus since the early Late Miocene, supporting the hypothesis that the sky islands constitute “museums” of ancient lineages. Lowlands and river valleys have acted as barriers preventing gene flow, while the montane archipelagos could have provided stepping stones to facilitate dispersal.

Species with moderate intraspecific trait variability are locally abundant within an environmentally heterogeneous subtropical forest - Guochun Shen; En-Rong Yan; Avi Bar-Massada; Jian Zhang; Heming Liu; Xihua Wang; Mingshan Xu (Oecologia, 2019)

Genome-Wide Classification and Evolutionary and Functional Analyses of the VQ Family - Hanyang Cai; Man Zhang; Yanhui Liu; Qing He; Mengnan Chai; Liping Liu; Fangqian Chen; Youmei Huang; Maokai Yan; Heming Zhao; Jerming Hu; Yuan Qin (Tropical Plant Biology, 2019)

The effect of mild acute psychological stress on attention processing: an ERP study - Mingming Qi; Heming Gao; Guangyuan Liu (Experimental Brain Research, 2018)

Iodine Status of Vulnerable Populations in Henan Province of China 2013–2014 After the Implementation of the New Iodized Salt Standard - Jin Yang; Lin Zhu; Xiaofeng Li; Heming Zheng; Zhe Wang; Yang Liu; Zongyu Hao (Biological Trace Element Research, 2016)

Inhibiting cyprinid herpesvirus-3 replication with CRISPR/Cas9 - Yicheng Zhao; Tiedong Wang; Ze Yu; Heming Wang; Bo Liu; Chunyan Wu; Chun-Bo Teng (Biotechnology Letters, 2016)

Serum Proteomic Analysis Based on iTRAQ in Miners Exposed to Soil Containing Rare Earth Elements - Heming Liu; Jianzhong Wang; Zenghua Yang; Kunzheng Wang (Biological Trace Element Research, 2015)

Fabrication of Carvedilol Nanosuspensions Through the Anti-Solvent Precipitation–Ultrasonication Method for the Improvement of Dissolution Rate and Oral Bioavailability - Dandan Liu; Heming Xu; Baocheng Tian; Kun Yuan; Hao Pan; Shilin Ma; Xinggang Yang; Weisan Pan (AAPS PharmSciTech, 2012)

A Framework for Evaluating the Effects of Human Factors on Wildlife Habitat: the Case of Giant Pandas - Jianguo Liu; Zhiyun Ouyang; William W. Taylor; Richard Groop; Yingchun Tan; Heming Zhang (Conservation Biology, 1999)
To address the complex interactions between humans and wildlife habitat, we developed a conceptual framework that links human factors with forested landscapes and wildlife habitat. All the components in the framework are integrated into systems models that analyze the effects of human factors and project how wildlife habitat would change under different policy scenarios. As a case study, we applied this framework to the Wolong Nature Reserve in Sichuan Province (southwestern China), the largest home of the giant panda ( Ailuropoda melanoleuca ). We collected ecological and socioeconomic data with a combination of various methods ( field observations, aerial photographs, government documents and statistics, interviews, and household surveys) and employed geographic information systems and systems modeling to analyze and integrate the data sources. Human population size has increased by 66% and the number of households in the reserve has increased by 115% since 1975, when the reserve was established. During the same period, the quality and quantity of the giant panda habitat dramatically decreased because of increasing human activities such as fuelwood collection. Systems modeling predicted that under the status quo, human population in the reserve would continue to grow and cause more destruction of the remaining panda habitat, whereas reducing human birth rates and increasing human emigration rates would lower human population size and alleviate human impacts on the panda habitat. Furthermore, our simulations and surveys suggested that policies encouraging the emigration of young people would be more effective and feasible than relocating older people in reducing human population size and conserving giant panda habitat in the reserve.